Kesehatan Lingkungan Kerja Home Industri Tembaga Kotagede Yogyakarta - Nur Ainun Simangunsong (Fakultas Hukum Universitas Islam Indonesia, 2003)
The health of work environmerit is the right of worker and the vital facility for optimal working productivity. As the right, the obligation of each work place create the health for work environment and it protects the health of workers through using approach maintenance, the health improvement (promotive the ill recovery (curative) and the health restoration (rehabilitation) taken holistically, comprehensively and continuously.